Dissolution and utilization of chitosan in a 1‐carboxymethyl‐3‐methylimidazolium hydrochloride ionic salt aqueous solution. Issue 22 (14th February 2015) - Feng, Jiaxuan; Zang, Hongjun; Yan, Qing; Li, Mingguang; Jiang, Xinqiang; Cheng, Bowen
ABSTRACT 1‐Carboxymethyl‐3‐methylimidazolium hydrochloride ([IMIM–COOH]Cl), a new ionic salt, is proposed as a green, promising solvent for dissolving chitosan. However, because of the optimal dosage of chitosan dissolved in [IMIM–COOH]Cl, a 12 wt % [IMIM–COOH]Cl aqueous solution was selected as an optimum solvent system for dissolving chitosan. The structures of the original and regenerated chitosan were characterized by Fourier transform infrared spectroscopy and X‐ray diffraction analysis. Scanning electron microscopy was used to visualize the morphological features of the reconstituted chitosan membranes. Meanwhile, the absorbance, tensile strength, and breaking elongation of the chitosan membranes were measured. The results reveal that 10–11 wt % was an optimal chitosan concentration for preparing membranes. Furthermore, the adsorption capacity for Cu(II) ion of the chitosan membranes was increased with the chitosan concentration decreased from 12 to 8 wt %. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41965.